IFMSA Research Exchange: A Life-Changing Experience - Tzioti, Maria Konstantina (International Journal of Medical Students, 2023)
Being an exchange student exhibits significant benefits beyond the educational scope, with regard to interacting with a different cultural environment, learning to accept diversity, acquiring the local language, and developing self-confidence. In this light, each year the International Federation of Medical Students’ Associations (IFMSA) provides the opportunity to approximately 15,000 medical students to carry out a clinical or research exchange in a foreign institution. In this article, I attempt to describe the unique journey I experienced in September 2022 in Argentina as a sophomore from Greece, not only in terms of educational and scientific knowledge, but also as far as cross-cultural interaction and personal growth.